On the Connection between the Dynamical System and the Ellis Compactification with Transitive Pointed System (Baghdad Science Journal, 2025)
In this paper, some relations between the flows and the Enveloping Semi-group were studied. It allows to associate some properties on the topological compactification to any pointed flows. These relations enable us to study a number of the properties of the principles of flows corresponding with using algebric properties. Also in this paper proofs to some theorems of these relations are given.